2020
DOI: 10.3390/ijms21249690
|View full text |Cite
|
Sign up to set email alerts
|

TCR Transgenic Mice: A Valuable Tool for Studying Viral Immunopathogenesis Mechanisms

Abstract: Viral infectious diseases are a significant burden on public health and the global economy, and new viral threats emerge continuously. Since CD4+ and CD8+ T cell responses are essential to eliminating viruses, it is important to understand the underlying mechanisms of anti-viral T cell-mediated immunopathogenesis during viral infections. Remarkable progress in transgenic (Tg) techniques has enabled scientists to more readily understand the mechanisms of viral pathogenesis. T cell receptor (TCR) Tg mice are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…The discovery of the chain-centricity phenomenon of some TCRs may have a substantial impact on TCR gene editing applications. For the generation of transgenic animals, the transgenesis of a single dominant active α-chain could produce animals with improved immunity without the significant alterations of the native TCR repertoire that occurs with the transgenesis of β-chains [ 17 , 18 ] or fully rearranged TCRs [ 19 ]. Our studies confirmed that this experimental approach can be used for the generation of transgenic animals with inheritable advanced anti-tumor immune defenses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the chain-centricity phenomenon of some TCRs may have a substantial impact on TCR gene editing applications. For the generation of transgenic animals, the transgenesis of a single dominant active α-chain could produce animals with improved immunity without the significant alterations of the native TCR repertoire that occurs with the transgenesis of β-chains [ 17 , 18 ] or fully rearranged TCRs [ 19 ]. Our studies confirmed that this experimental approach can be used for the generation of transgenic animals with inheritable advanced anti-tumor immune defenses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key features of adaptive immunity is the enormous receptor diversity of lymphocytes, which is estimated to cover over 10 10 unique sequences for T cells alone ((Cho et al, 2020; Lythe et al, 2016). This empowers the adaptive immune system to tackle an infinite number of invaders.…”
Section: Introductionmentioning
confidence: 99%
“…In the fever phase, it was significantly elevated [4]. In addition, the diversity of T and B cell receptors is of great significance for the research and treatment of infectious diseases [5,6]. However, the diversity characteristics of TCR and BCR in HFRS remain unclear.…”
Section: Introductionmentioning
confidence: 99%